2000
DOI: 10.1034/j.1399-3003.2000.16b26.x
|View full text |Cite
|
Sign up to set email alerts
|

Update on sputum methodology

Abstract: Over the past few years cellular and biochemical sputum examinations have become important instruments to assess airway inflammation. The aim of this review is to summarize new methodological developments and aspects, which are currently under investigation.The use of isotonic saline has increased safety of inductions in patients with severe asthma and in children. The origin of sputum is better understood, as is the need to standardize the volume and duration of induction. It also needs to be borne in mind th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
7

Year Published

2003
2003
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 44 publications
(37 reference statements)
0
33
0
7
Order By: Relevance
“…During the initial minutes components of the central airway are sampled with predominance of neutrophils and during the final minutes the distal airways are sampled together with the alveolar compartment giving a predominance of macrophages. 20,21 The quality of the material analyzed depends on the time passed before the start of sputum processing, on the number of squamous cells present in the sample and on the quantity of inflammatory cells analyzed. 16 Ideally, it is suggested that sputum should be processed within 2 hours of collection.…”
Section: Discussionmentioning
confidence: 99%
“…During the initial minutes components of the central airway are sampled with predominance of neutrophils and during the final minutes the distal airways are sampled together with the alveolar compartment giving a predominance of macrophages. 20,21 The quality of the material analyzed depends on the time passed before the start of sputum processing, on the number of squamous cells present in the sample and on the quantity of inflammatory cells analyzed. 16 Ideally, it is suggested that sputum should be processed within 2 hours of collection.…”
Section: Discussionmentioning
confidence: 99%
“…Spirometry, including a bronchodilation test, was performed in all subjects using a computerised system (MasterLab 2.12; Jaeger, Wü rzburg, Germany) according to standardised guidelines [26].…”
Section: Spirometrymentioning
confidence: 99%
“…The adverse response occurs despite prior administration of a b 2 -agonist, which is strongly recommended for sputum induction [6]. Besides the inability of a b 2 -agonist to afford complete protection, little is known about the protective measures against the effects of hypertonic saline in COPD.…”
mentioning
confidence: 99%